COVID-19-associated encephalitis. - Braidy Sutton; Damian Honeyman; Adriana Notaras; Ashley Quigley (Global Biosecurity, 2023)
COVID-19 associated encephalitis has been reported in patients infected with SARS-CoV-2 since February 2020. The index case was reported in Japan, but since then, reports have emerged worldwide, with a global incidence rate of 0.215%, and regional incidence rates of up to 18%. While in the acute phase of infection, COVID-19-associated encephalitis can biologically mimic infectious limbic encephalitis, immune-inflammatory-mediated encephalopathy, herpes simplex encephalitis, produce hyperintensities in multiple regions of the brain, and mimic Alzheimer’s Disease. With a high mortality rate of 13.4%, COVID-19-associated encephalitis poses a significant burden on health systems and resources, requiring a combination diagnostic approach, supportive treatment regimens, and regular monitoring for secondary worsening of symptoms. COVID-19-associated encephalitis can emerge up to six weeks post-infection, and elevated risk levels can persist for six months post-infection. Despite emerging evidence and research, significant longitudinal research is required to ascertain the true prevalence and lifetime health risk of developing encephalitis following SARS-CoV-2 infection. This report aims to provide a summary of COVID-19 associated encephalitis.